Pengaruh Capital Adequacy Ratio, Loan to Deposit Ratio & Return on Assets terhadap Perubahan Laba (Studi Empiris pada Perusahaan Perbankan yang Listed di BEJ) - Siti Marlina; Ratna Ratna (CITRA EKONOMI, 2021)
The purpose of this study was to determine the effect of capital adequacy ratio, loan to deposit ratio & Return On Assets to changes in earnings. In this study using the type of quantitative research. Data analysis tools used multiple regression, T test, F test and determination. The results of the partial test showed that CAR, LDR and ROA had a significant effect, on the T-test CAR and ROA had an effect on changes in profit, in the F Car test, LDR and ROA had an effect on changes in earnings. Simultaneously CAR, LDR, and ROA have a significant effect on changes in profit for the next one year in banking companies listed on the BEJ. The magnitude of the influence is 15.9% and the remaining 84.1% is influenced by other variables outside the study. So it can be concluded that the ability of the independent variable is very small to detect changes in earnings in this study, which is only 15.9%.